Legal Legism in the Era of the National Criminal Code: The Prosecutor's Office as a Fair Law Enforcer - Resta, Ngurah Wahyu; Swardhana, Gde Made; Kasih, Desak Putu Dewi; Purwani, Sagung Putri M.E. (Ridwan Institute, 2025)
The enactment of Law Number 1 of 2023 concerning the Criminal Code (National Criminal Code) affects the duties and functions of the Prosecutor's Office as a law enforcer, which has tended to be formalistic and procedural, thus encouraging this institution to place more emphasis on fulfilling the principles of justice, the effectiveness of law enforcement, and the protection of victims' rights, while strengthening its strategic role in the prevention and prosecution of criminal acts in accordance with the new norms in the Criminal Code. However, the recognition of the National Criminal Code regarding the existence of living law in society other than written law creates tension between legal certainty and substantive justice (social justice). Prosecutors face a dilemma when an act that is recognized as criminal under customary law is not written in the law, thus creating legal uncertainty in the practice of prosecution. The result of this study is the principle of formal legality Article 1 paragraph (1) of the National Criminal Code which is linear with the view of the school of legalism emphasizes that every act can only be punished based on written law, ensuring legal certainty and protection of human rights. The enactment of Article 2 of the National Criminal Code, the principle of legality has expanded its meaning, which in its regulation recognizes the laws that live in society (living law) and social values, customary norms, and substantive justice in the sense of the principle of material legality. The real implementation can be seen in the innovation of the Bali High Prosecutor's Office through Bale Kertha Adhyaksa Jaga Desa and Umah Restorative Justice, which integrates positive law and customary law of Tri Hita Karana. The Prosecutor's Office now plays an adaptive, humanist, and fair role, guarding social harmony as well as legal certainty.